Optimizing the Construction of Gyro Sensitive Elements Based on Bulk Acoustic Waves - Durukan, Yasemin; Popkova, Ekaterina S.; Marina, A. Rybina; Shevelko, Michail M. (2019 International Conference "Quality Management, Transport and Information Security, Information Technologies" (IT&QM&IS), 2019)
The possible trends for gyro sensitive element construction optimization are discussed for the case when the bulk acoustic wave properties under rotation are the informative signal. The promising materials for creating acoustic duct and piezoelectric transducer, which make it possible to decrease sensitive element size for the same informative signal level, are considered.